A previously treated severe haemophilia A patient developed high-titre inhibitor after vaccinations. (July 2020) - Li, Zekun; Chen, Zhenping; Cheng, Xiaoling; Wu, Xinyi; Li, Gang; Zhen, Yingzi; Poon, Man-Chiu; Wu, Runhui
The factor VIII (FVIII)-neutralizing antibody (inhibitor) seen in 25%–30% of patients with severe haemophilia A (SHA). Vaccination is a non-genetic risk factor of inhibitor development as 'danger signal' which may provide a pro-inflammatory microenvironment to increase FVIII immunogenicity. We reported a previously treated SHA patient postponed the first vaccination to 15-month age received diphtheria-pertussis-tetanus intramuscularly. At 18-month age, the patient received Hepatitis A intramuscularly and Varicella Zoster Virus subcutaneously with 2 weeks interval and FVIII infusion was given <24 h prior for each. Successive bleedings occurred 1 week later with inefficacy of FVIII replacement. High-titre inhibitor was tested at 117 exposure days. This case suggested that continuous vaccinations in close proximity to FVIII could induce inhibitor. The relationship between vaccination and FVIII immunogenicity still needs to be revealed by further study.